Pemalangan Tanah Sebagai Bentuk Resistensi Masyarakat Papua Barat Terhadap Pembangunan - Ngabalin, Marthinus; Adi, Suwarto; Tampake, Tony (Indonesian Journal of Religion and Society, 2024)
This research aims to analyze the resistance efforts of West Papuans in land blocking in the form of demands for compensation, customary bars, complaints and demands, coordination with other parties and the use of traditional leadership systems. In Papuan culture, talking about land means talking about people at the same time. On the other hand, this research also analyzes the phenomenon of land blocking as a form of resistance to the development process in Papua. This stems from the concept that development that does not involve the community in the planning process will have an impact on the process. Resistance is seen as a model of resistance to the development process in the form of rejection, blockading and even carried out openly in the form of protests and demonstrations. The method used is qualitative research, using an ethnographic approach. Data collection techniques were carried out by observation, interviews and literature studies. Data analysis in the study adopted the Miles and Huberman interactive model which includes data reduction, data presentation, and conclusion drawing. The research findings show that land for the Papuan people has a very important role in life and is interpreted as Mama who contains and gives life to humans. In addition, resistance is understood as a form of protest against the development process carried out on the land of the Papuan people